SOCS, Inflammation, and Autoimmunity - Yoshimura, Akihiko; Suzuki, Mayu; Sakaguchi, Ryota; Hanada, Toshikatsu; Yasukawa, Hideo (Frontiers in Immunology, 2012)
Cytokines play essential roles in innate and adaptive immunity. However, excess cytokines or dysregulation of cytokine signaling will cause a variety of diseases, including allergies, autoimmune diseases, inflammation, and cancer. Most cytokines utilize the so-called Janus kinase–signal transducers and activators of transcription pathway. This pathway is negatively regulated by various mechanisms including suppressors of cytokine signaling (SOCS) proteins. SOCS proteins bind to JAK or cytokine receptors, thereby suppressing further signaling events. Especially, suppressor of cytokine signaling-1 (SOCS1) and SOCS3 are strong inhibitors of JAKs, because these two contain kinase inhibitory region at the N-terminus. Studies using conditional knockout mice have shown that SOCS proteins are key physiological as well as pathological regulators of immune homeostasis. Recent studies have also demonstrated that SOCS1 and SOCS3 are important regulators of helper T cell differentiation and functions. This review focuses on the roles of SOCS1 and SOCS3 in T cell mediated inflammatory diseases.